A Quantitative Method to Measure and Speciate Amines in Ambient Aerosol Samples - Amy P. Sullivan; Katherine B. Benedict; Christian M. Carrico; Manvendra K. Dubey; Bret A. Schichtel; Jeffrey L. Collett (Atmosphere, 2020)
Ambient reactive nitrogen is a mix of nitrogen-containing organic and inorganic compounds. These various compounds are found in both aerosol- and gas-phases with oxidized and reduced forms of nitrogen. Aerosol-phase reduced nitrogen is predominately thought to include ammonium and amines. In ambient samples, the ammonium concentration is routinely determined, but the contribution of amines is not. We developed a method to discretely measure amines from ambient aerosol samples. It employs ion chromatography using a Thermo Scientific IonPac Dionex CS-19 column with conductivity detection and a three-step separation using a methanesulfonic acid eluent. This method allows for the quantification of 18 different amines, including the series of methylamines and the different isomers of butylamine. Almost all amines quantifiable by this technique were measured regularly when applying this method to ambient filter samples collected in Rocky Mountain National Park (RMNP) and Greeley, CO. The sum of the amines was ~0.02 µg m−3 at both sites. This increased to 0.04 and 0.09 µg m−3 at RMNP and Greeley, respectively, at the same time they were impacted by smoke. Analysis of separate, fresh biomass burning source samples, however, suggests that smoke is likely a minor emission source of amines in most environments.